Geochemical evidence of the indirect pathway of terrestrial particulate material transport to the Okinawa Trough. (16th June 2017) - Chen, Chen-Tung Arthur; Kandasamy, Selvaraj; Chang, Yuan-Pin; Bai, Yan; He, Xianqiang; Lu, Jung-Tai; Gao, Xuelu
Abstract: The major source of particulate matter in the East China Sea (ECS) is the Changjiang (Yangtze) River. Sediment types, the geochemical indices of terrigenous and biogenic inputs (TOC, CaCO3 and Sc), and biomarker indices such as the carbon preference index (CPI) of long-chain n-alkanes and the cinnamyl/vanillyl ratio (C/V) in surface sediments, all reveal that the influence of terrestrial material initially declines away from the mouth of the Changjiang River across the ECS continental shelf. However, the influence then strengthens from the middle ECS shelf toward the continental slope and the Okinawa Trough, because when the northeast winds prevail from September to April, the Changjiang River plume flows southwestward along the coast of China. Part of this flow turns eastward in the northern Taiwan Strait, and then joins the northeastwardly flowing Kuroshio to reach the Okinawa Trough. As the central ECS is bypassed, the sediments accumulated there are geologically older, carbonate-rich and organic-poor than those found off the coast of China and in the Okinawa Trough. Between June and August, when southwest winds prevail, the Changjiang plume generally flows northeastward. Yet, strong cyclonic currents that are generated by typhoons that pass through the ECS move the suspended particulates and the resuspended sediments southwestward from the coast of China. The turbid water then turns toward Taiwan in the northern Taiwan Strait and joins the Kuroshio, before reaching the Okinawa Trough. Again, young sediments are transported to the Okinawa Trough without passing through the central ECS.